Identification of metabolic reprogramming-related key genes in hepatocellular carcinoma after transcatheter arterial chemoembolization treatment - Tongfei Li; Shujuan Liu; Shengjun Wang; Shan Sun; Feng Ji; Mingliang Li; Yong Zhang (Discover Oncology)
Abstract Background Metabolic reprogramming plays an important role in therapeutic efficacy of hepatocellular carcinoma (HCC). However, the metabolic reprogramming-related key genes associated with transcatheter arterial chemoembolization (TACE) treatment sensitivity in HCC remain further investigation. Methods We analyzed data from public databases, The Cancer Genome Atlas and Gene Expression Omnibus, as well as metabolism-related genes (MRGs), to identify key genes associated with TACE treatment sensitivity. Further analysis was conducted on the relationship between key genes and immune cell infiltration, HCC-related genes, regulatory network construction, nomogram construction, and drug sensitivity analysis. Finally, the expression of key genes was validated based on databases and in vitro RT-qPCR. Results Four key genes (CDC20, LPCAT1, PON1, and SPP1) associated with TACE treatment sensitivity were identified. Increased CDC20, LPCAT1, and SPP1 and reduced PON1 were found in tumor tissues than normal tissues, as well as in advanced patients than early-stage patients. Lower expression of CDC20, LPCAT1, and SPP1, and higher expression of PON1 were detected in responsive patients than non-responsive patients. Patients with high expression of CDC20, LPCAT1, and SPP1, and low expression of PON1 had poor prognosis. They were also correlated with tumor immune microenvironment and sensitivity to multiple chemotherapy drugs. The expressions of key genes at the gene and protein levels were validated. Conclusions Our study provided systematic insights into identification of biomarkers for TACE treatment sensitivity in HCC.